IPhone JavaScript cookbook : clear and practical recipes for building web applications using JavaScript and AJAX without having to learn Objective-C or Cocoa /: clear and practical recipes for building web applications using JavaScript and AJAX without having to learn Objective-C or Cocoa. (2011) - Unknown
No abstract available